Carpet displayed on a wall at the Parsee Mazagaon Anjuman Daremeher - Mumbai Archive Project Team (Jio Institute, 2024)
In addition to antique wooden furniture, the Parsee Mazagaon Anjuman Daremeher displays various items associated with the Zoroastrian faith. This carpet, for example, has representations of the Farvahar, Lamassu, and various kings of the Achaemenid Empire, which was based in ancient Persia.